“Government by Trading Company?: the corporate legal status of the Company of New France and Colonial Governance” - Dewar, Helen (Nuevo Mundo Mundos Nuevos, 2018)
This article takes the Company of New France or CNF (1627-1663) as a case study to consider the legal dimensions of early modern chartered companies – how they established themselves, how they dealt with disputes, and how they exercised the regal powers delegated to them. Drawing on recent literature that challenges the entrenched notion of companies as exclusively economic entities, it considers the Company of New France as an experimentation with new tools of capital formation and governance. The article puts the CNF in comparison with other corporations and commercial associations in France as well as contemporary chartered companies in the Atlantic. While the company shared certain characteristics with other French corporations, notably a separate legal personality, responsibility for internal governance, and a contractual relationship with the king, as an overseas commercial and colonizing enterprise, the nature of its privileges, functions, and obligations were distinct. The paper’s final section considers challenges faced by the CNF in the execution of its mandate, particularly with the establishment of a new, ostensibly subordinate corporation, the Communauté des Habitants in 1645. The frictions between these two bodies underscore the inextricable ties between trade and effective governance in the colony.
Keywords: New France; chartered companies; corporations; governance; law